The wisdom of ecofeminism in Arjasari as a link between Hadith and community practice - Daffa, Muhammad; Purnamasari, Dyah (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
This research aims to discuss ecological wisdom in Arjasari as a link between hadith and community practice. This qualitative research used a case study. It used hadith science theory as the formal object, and the practice of ecofeminism the material object. Using observation, interviews, and documentation for data collection, this study analyzed the data through inventory, classification, and interpretation stages. The research involved two community organizations affiliated with the Sapa Institute: Bale Istri Community and Islamic Organization in Arjasari, Bandung, Indonesia, from July 2022 to December 2022. This research is unique because it explores thematic hadiths, which serve as a basic source for integrating Islamic teachings into the practice of ecofeminism. This study explores the matan of traditions related to ecology, using a thematic approach to understand their relevance to contemporary environmental challenges comprehensively. The research shows that ecofeminism practices of community organizations from the perspective of hadith were found in Arjasari Village, Bandung. The identified hadiths emphasize responsible land use, sustainable agriculture, and preservation of natural resources, contributing to developing an ecofeminist framework in Arjasari, harmonizing Islamic values with environmental ethics. This study's unique contribution lies in exploring thematic hadith, which integrates ecofeminist practices. The deliberate linkage of religious principles with ecofeminist discourse promotes the equivalence between environmental standards and Islamic values.